Reduced hemolytic complement activity in the classical pathway (CH50) is a risk factor for poor clinical outcomes of patients with infections: a retrospective analysis of health insurance claims in Japan - Koami, Hiroyuki; Furukawa, Yutaro; Hirota, Yuri; Sasaki, Akira; Ogawa, Hirotaka; Matsuoka, Ayaka; Shinada, Kota; Nakayama, Kento; Sakurai, Ryota; Iwanaga, Sachiko; Onohara, Takayuki; Narumi, Shogo; et al. (Frontiers in Immunology, 2025)
PurposeTo evaluate whether low CH50 (a comprehensive measure of hemolytic activity of the classical complement pathway) is associated with infection-related coagulopathy, organ dysfunction, and poor clinical outcomes.MethodsThis was a retrospective study using Japanese health insurance claim data (2014-2023). Adult patients whose CH50 values were measured within one week of admission were included. We divided the patients into three groups based on the normal CH50 range: Low CH50 (< 25 U/mL; n=168), Normal CH50 (25 ≤, < 48 U/mL; n=1273), and High CH50 (48 ≤ U/mL; n=1285).ResultsOf 2,726 patients who met the inclusion criteria, logistic regression models demonstrated that decreased CH50 is a significant predictor of 180-day mortality (OR: 0.98-0.99). Cumulative survival rates in the Low CH50 group at 28 days and 180 days were both unfavorable (both p < 0.0001, Log-rank test). CH50 was significantly inversely correlated with SOFA, SIC, ISTH-overt DIC, and JAAM-2 DIC scores, and was also correlated with C3 and C4 levels. Diminished CH50 may be particularly useful in diagnosing SIC (specificity; 79.2%) and excluding ISTH-overt DIC (sensitivity; 90.5%). Moreover, patients with low levels of both CH50 and C3 had an extremely high mortality rate (25.0%).ConclusionLow CH50 after infection is not only significantly associated with multiple organ failure and coagulopathy but is also an independent risk factor for poor prognosis. Complement activation after infection may help to avert organ damage and to improve clinical outcomes.